(untitled) (Bangladesh Medical Journal, 2014)
An interventional study was carried out in the department of Dermatology and Venereology, Faridpur Medical College Hospital, Bangladesh from January, 2010 to June 2010 to evaluate the efficacy of topical doxepin cream in eczematous dermatoses. We included ninety three patients with moderate to severe pruritic eczematous dermatoses, in this study. Improvement of pruritus was assessed at day 3 and at day 7 by both Visual analogue scale (VAS) and Itch severity) scale (ISS). By VAS at day 3, 61.3% patients showed improvement and at day 7 improvement rate increases to 84.9%. By ISS, improvement at day 3 was 68.9%, and increased to 90.3% at day 7. Improvement was experienced by all types of eczema patients. By visual analogue scale (VAS) mean pruritus reduction at day 3 was 2.25 (± 1.93) and at day 7 was 4.30 (± 1.99). By ltch Severity Scale (ISS) mean pruritus reduction at day 3 was 3.76 (± 2.91), and at day 7 was 8.18 (± 3 42). An average of 27.27% (29.88% by VAS and 24.65% by ISS) reduction of pruritus noticed at the end of day 3 and at the end of study, response increases to 55.58% (57.10% by VAS and 54.06% by ISS) Paired sample t test was done and found that pruritus reduction was statistically significant at day 3 and day 7 both by VAS & ISS We can conclude that doxepin cream is highly effective in relieving pruritus associated with eczematous dermatoses but it has little effect on eczema itself. DOI: http://dx.doi.org/10.3329/bmj.v41i3.18955 Bangladesh Medical Journal 2012 Vol.41(3): 28-32